SLEEP QUALITY AND RELATED FACTORS AMONG REGULAR STUDENTS AT HUE UNIVERSITY OF MEDICINE AND PHAMACY, HUE UNIVERSITY (Vietnam Journal of Community Medicine, 2026)
Objective: Assess sleep quality on a Pittsburgh scale and find out some factors related to sleep quality in regular students of the Hue University of Medicine and Pharmacy, Hue University.Method: A cross-sectional study was conducted from December 2021 to January 2022 for data were collected by self-filling a set of prepared questionnaires. The variables analyzed by SPSS 20.0 software to determine the relationship between sleep quality and risk factors.Results: 39% of students have poor sleep quality. Results of multivariate regression analysis showed that factors associated with sleep quality included the proportion of students who tested positive for COVID-19 in the past month, academic anxiety due to COVID-19 in the past month, moderate anxiety, and moderate stress (p < 0.05).Conclusion: Students need to be more fully equipped with their sleep hygiene measures, especially after having COVID-19. The university, families need to pay more attention to study regimes, exams, rest to help improve the sleep quality and psychology of medical students.
Keywords: Pittsburgh sleep quality idex (PSQI), sleep quality, student.